Diagnostic Accuracy Of Slit Skin Smear and FNAC in Diagnosis of Cutaneous Leishmaniasis Taking Histopathology as Gold Standard - Yasin Khan, Muhammad Farooq, Nighat Fatima, Seemab Khan, Shagufta Irum (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the efficacy of slit skin smear and fine-needle aspiration cytology (FNAC) for diagnosing cutaneous leishmaniasis while keeping histopathological analysis as a gold standard. Place and duration of study: From 6th Jan 2020 to 6th Jan 2021 at Bakhtawar Amin Medical & Dental College, Multan. Study design: A Cross-Sectional Study Methodology: In this study, a total of 180 patients were observed. In the slit skin smear technique, the Smear was fixed and stained with Leishman or Giemsa stain. For the FNAC technique, hematoxylin and eosin (H & E) stained smear slides were prepared which were examined under light power. For FNAC, the stained slides were examined under low (10x) and high power (40x) to examine cell mass and product formation and then under oil immersion lens (100x) for identifying the morphology of the parasite. Results: The diagnostic accuracy of slit skin smear was 44.44% and that of fine-needle aspiration cytology was 88.33%. Conclusion: Fine needle aspiration cytology has better diagnostic accuracy as compared to slit skin smear in diagnosing cutaneous leishmaniasis.